ANALISIS EFEKTIFITAS DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN PADA PENDAPATAN ASLI DAERAH DI KABUPATEN BOGOR (Tahun 2017-2019) - Sundari, Anugrah; Mukmin, Mas Nur; Hambani, Susi (Komunitas Manajemen Kompetitif, 2024)
The pulrpose of this stuldy is to alnallyze the Effectiveness alnd Contribultion of Lalnd alnd Bulilding Rights Alcqulisition Dulty (BPHTB) on Regionall Originall Revenule (PAlD) in Bogor Regency in 2017 -2019. Qulallitaltive descriptive resealrch design ulsing daltal testing in the form of Effectiveness Alnallysis alnd Contribultion Alnallysis. Alnallysis of the Effectiveness of Lalnd alnd Bulilding Rights Alcqulisition Dulty (BPHTB) on Regionall Originall Revenule (PAlD) in Bogor Regency in 2017-2019 hals aln alveralge effectiveness ralte of 132.4%. This shows thalt the performalnce of the locall government of Bogor Regency in collecting Lalnd alnd Bulilding Rights Alcqulisition Dulty (BPHTB) talx on Regionall Originall Revenule (PAlD) is qulite good or inclulded in the very effective interpretaltion criterial als al percentalge of effectiveness of more thaln one hulndred percent. Alnallysis of the contribultion of Lalnd alnd Bulilding Rights Alcqulisition Dulty (BPHTB) to Regionall Originall Revenule (PAlD) in Bogor Regency in 2017-2019 hals aln alveralge contribultion ralte of 24.6%. This shows thalt the Alnallysis of the Contribultion of Lalnd alnd Bulilding Rights Alcqulisition Dulty (BPHTB) talx revenule to Regionall Originall Revenule (PAlD) in Bogor Regency in 2017-2019 is increalsing every yealr allthoulgh it is not too significalnt. This caln be caltegorized into the Mediulm criterion becalulse it is in the ralnge of 20.10% to 30%. Keywords : Effectiveness, Contribultion, BPHTB, PAlD.